IMPLEMENTASI KURIKULUM MADRASATUL MUALLIMIN AL-ISLAMIYAH (MMI) DALAM MENINGKATKAN PRESTASI BELAJAR MEMBACA KITAB KUNING SANTRI KELAS ULYA DI PONDOK PESANTREN AL-FURQON WEDOROANOM DRIYOREJO GRESIK - Hawari Em Mashuri; Eli Masnawati; Masfufah (EDUSIANA: Jurnal Manajemen dan Pendidikan Islam, 2025)
This study aims to describe the implementation of the Madrasatul Muallimin Al-Islamiyah (MMI) curriculum in improving the learning achievement of students in the Ulya class in reading yellow books at the Al-Furqon Wedoroanom Islamic Boarding School, Driyorejo, Gresik. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the MMI curriculum is a curriculum based on Islamic boarding school traditions designed to produce cadres of ulama through strengthening classical Islamic material, especially yellow books. The curriculum implementation is carried out through structured learning, intensive guidance, and the sorogan and bandongan methods. The students' achievement has increased significantly in understanding the structure of classical Arabic and the contents of the books. Supporting factors for the implementation of this curriculum are teacher competence, a conducive Islamic boarding school environment, and student motivation. Meanwhile, inhibiting factors include limited time, heterogeneity of student abilities, and minimal mastery of mufrodat. The recommendations of this study are improving teacher training, learning facilities, and periodic evaluations.